Investment in Renewable Energy: A Case Study of North Africa - Okba mekhnane; Lazhari Zouaouid (African Journal of Advanced Pure and Applied Sciences, 2024)
This research paper aims to shed light on the reality of investment in renewable energies in North African countries, exploring their fields and investment prospects. The study concluded that the region has an ideal potential to create an integrated system that will produce renewable energy, liberate vast quantities of water, air condition living and working spaces, and create jobs without adding to the burden on Mother Earth. Large areas of North Africa with high levels of sunshine and high-quality solar radiation are potential sites to exploit the sun’s lending of energy free of charge.